2020
DOI: 10.1186/s13071-020-04383-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor FTZ-F1 regulates mosquito cuticular protein CPLCG5 conferring resistance to pyrethroids in Culex pipiens pallens

Abstract: Background Culex pipiens pallens poses a serious threat to human health because of its widespread distribution, high carrier capacity for several arboviruses, frequent human-biting, and growth in urban environments. Pyrethroid insecticides have been mainly used to control adult Cx. pipiens pallens during outbreaks of mosquito-borne diseases. Unfortunately, mosquitoes have developed resistance, rendering the insecticides ineffective. Cuticular resistance is the primary mechanism of pyrethroid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…The over-expression of CP genes in resistant strains led to the increased thickness of cuticle, resulting in a cuticular penetration resistance to insecticide. Due to CP genes that exhibit higher expressions in resistant strains than in susceptible strains with the most potential to be implicated in insecticide resistance [19,21,36,42], CP genes of FAW up regulated here are worth being focused on to investigate their role in insecticide resistance. In addition to induction, CP genes can also be reduced by insecticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The over-expression of CP genes in resistant strains led to the increased thickness of cuticle, resulting in a cuticular penetration resistance to insecticide. Due to CP genes that exhibit higher expressions in resistant strains than in susceptible strains with the most potential to be implicated in insecticide resistance [19,21,36,42], CP genes of FAW up regulated here are worth being focused on to investigate their role in insecticide resistance. In addition to induction, CP genes can also be reduced by insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the mixture of CPs, they greatly contribute to determine the properties of the insect cuticles for defending against environmental stresses [16,17]. Previous reports have shown that the changed expression of CP genes is associated with the exposure to insecticides, indicating that CPs participate in insecticide resistance [18][19][20][21]. However, the precise roles served by CPs in response to insecticides remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cuticle proteins play an important role in insect cuticle resistance, by thickening the cuticle to prevent the penetration of insecticides, and changing the density, thickness and insect morphological development of the cuticle. There is increasing evidence that alteration of the cuticle plays a role in insecticide resistance, based on analysis of CP transcripts and measurement of cuticle thickness [19,21,22,23,24,25]. For example, CYP4G16, CPLCG3, CPLCG5 and CPLC8 have been implicated in insecticide resistance by contributing to a thicker cuticle and thereby slowing penetration of insecticides [21,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the cuticle was examined using image J software. The other detailed steps of the TEM experiment have been described in previous studies [14,19].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation